Prospective study to assess knowledge regarding wheezing disorders among mothers of children aged between 6 months to 10 years: hospital based study - Kumar, Naresh; Malik, Supriya (International Journal of Contemporary Pediatrics, 2018)
Background: Asthma is a heterogeneous disease, usually characterized by chronic airway inflammation. It is defined by history of Respiratory symptoms, most common being wheeze, shortness of breath, chest tightness and cough that vary over time. Medical professionals are trained to manage and prevent asthma exacerbations, however prevailing environmental triggers along with non adherence to medical advice are major challenges in prevention of asthma exacerbations. This occurs because of poor parental knowledge regarding the disease. Parents specially Mother play crucial role in preventing & Management of acute exacerbation of Asthma at home. The objective of this study was to assess maternal knowledge regarding wheezing disorders a among children aged between 6 month - 10 years. Methods: The present study is a prospective study, carried out at department of pediatrics, at Sri Guru Ram Das Institute of Medical Sciences and Research, Amritsar from October 2016 - January 2018 over period of 15 months. Total 275 mothers of children aged between 6 month -10 years when enrolled as sample. The Aim of the study was to assess knowledge of mothers of wheezing children between 6 month-10 years and to educate and counsel mothers about home management of wheezing episode. Results: Early recognition of asthma exacerbations at home in order to intensify treatment early can often prevent worsening of asthma. Lack of skill and cooperation is most common cause for aerosol delivery problems in children. The present study shows that although 80% of the mothers were aware of aerosol therapy but only 37.8% were using it at time of sudden wheezing attack at home. About 14.9% mothers considered using steam inhalation and 37% mothers using medications prescribed at time of previous attack beneficial. Conclusions: The present study was conducted to asses knowledge about asthma in mothers of children aged between 6 month-10 years having wheezing disorders. Study revealed that mothers had poor knowledge about home management of an acute attack of asthma. Asthma management programmes should focus on augmenting awareness of parents, eliminate social stigma and misconceptions regarding asthma in community. This study is a step towards it.